Development and Multiplexed Amplification of SSR Markers for Thuja occidentalis (Cupressaceae) Using Shotgun Pyrosequencing - Xu, Huaitong; Tremblay, Francine; Bergeron, Yves (Applications in plant sciences, 2013)
Premise of the study: Sixteen novel, polymorphic, multiplexed microsatellite loci were developed for eastern white cedar (Thuja occidentalis) using simple sequence repeat (SSR)–enriched shotgun pyrosequencing. Methods and Results: Sixteen loci were tested on a panel of 24 individuals from different populations. The number of observed alleles ranged from four to 22. Four sets of multiplex PCR for the 16 loci were then carried out on 60 individuals of two populations from islands of FERLD Duparquet Forest, Canada. Mean number of alleles, observed heterozygosity, and expected heterozygosity were respectively 5.75, 0.594, and 0.574 for Island 58, and 5.50, 0.704, and 0.624 for Island 134. Conclusions: Four sets of multiplex microsatellite loci can be used for future genetic studies, which includes investigating genetic diversity and structure, and fragmentation and regeneration studies.